الحكم الدولي محمد لمين بن عسيى وصافرة التحكيم في كرة القدم. - زواوي عبد الوهاب; اشراف أحمد المهدي الزواوي (جامعة محمد بوضياف -المسيلة, 2024)
تهدف هذه الدراسة الى تسليط الضوء على إحدى الشخصيات الرياضية التي لعبت دورا في الرياضة وسلك التحكيم في كرة القدم محليا ووطنيا ودوليا ، ابنولاية المسيلة الحكم الدولي "بن عيسى محمد لمين " وذلك اعتمادا على شهادته الحية ومجموعة من المعطيات والمعلومات و الوثائق التي تكشف عن سيرتةومسيرتةالرياضية في سلك التحكيم وعمله في قطاع الصحة ، شاركت هذه الشخصية في النشاط الرياضيبالمسيلة، لقد تميز "بن عيسى محمد لمين " بمساهمة فعالة ومهام عديدة في ما بتعلق بالتحكيم والتدريب والتكوين على الصعيدين الوطني والدولي ، والحقيقة عرف بنشاطه وصرامته الكبيرة واخلاقه العالية ، ولهذا اطلق عليه لقب المخلص في مساره التحكيمي وحبه لصافرة التحكيم ، وهذا ما يستوجب علينا نحن ابناء وجيل اليوم ان نستلهم العبر من مشواره الرياضي وتضحياته في سبيل ان تبقى الجزائر ممثلة في التحكيم الدولي بعزتها وشموخها من خلال البناء والتشييد وتكوين الاطارات في كل المجالات التي من شأنها الحفاظ على رسالة المجاهدين والشهداء على غرار ماقدمه لاعبو فريق جبهة التحرير الوطني لكرة القدم . Study summary: This study aims to shed light on one of the sports figures who played a role in sports and the football refereeing field locally, nationally and internationally, the son of the M’sila state, the international referee “Ben Issa Mohamed Lamin”, based on his live testimony and a set of data, information and documents that reveal his biography. His sports career is in arbitration and his work in the health sector. This personality participated in sporting activity in M’sila. “Ben Issa Mohamed Lamine” was distinguished by his effective contribution and many tasks related to arbitration, training and formation at the national and international levels. In fact, he was known for his activity, great strictness and high morals, and for this reason he was called the savior in his arbitration career and his love for the refereeing whistle. This is what requires us, the children and generation of today, to draw lessons from his sporting career and his sacrifices in order for Algeria to remain represented in international arbitration with its pride and dignity through building, construction and training of tires in all fields that would preserve the messageof the mujahideen and martyrs, similar to what the players of the Front team presented. National Football Liberation. .